2009
DOI: 10.1145/1543135.1542528
|View full text |Cite
|
Sign up to set email alerts
|

Trace-based just-in-time type specialization for dynamic languages

Abstract: Dynamic languages such as JavaScript are more difficult to compile than statically typed ones. Since no concrete type information is available, traditional compilers need to emit generic code that can handle all possible type combinations at runtime. We present an alternative compilation technique for dynamically-typed languages that identifies frequently executed loop traces at run-time and then generates machine code on the fly that is specialized for the actual dynamic types occurring on each path through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 8 publications
(2 reference statements)
0
81
0
Order By: Relevance
“…A lack of formal benchmark sets for scripting languages make these suites a common source of benchmarking for scripting language implementations [10,3,6,17].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A lack of formal benchmark sets for scripting languages make these suites a common source of benchmarking for scripting language implementations [10,3,6,17].…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown the advantages of type specialization in JIT compilation [19,10]. However, little research exists on the specialization of interpreters for scripting languages.…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations